Procedural aspects concerning maritime law - Fontestad-Portalés, Leticia (My University, 2016)
Along this work we wish to highlight the main influence of Procedural Law in some as-pects in our Maritime Law. Our point of view has been supported by new Maritime Naviga-tion Act of 2014, when including the Title X ruling "Procedures Specialities in Maritime Navigation". We are focusing on the Bill of Lading as an essential document in maritime shipping from a procedural point of view. It is particulary relevant the express recognition of its enforce-able nature through the Spanish Maritime Navigation Act, giving to the bill of lading the consideration as an true extrajudicial enforceable title. We will point out the main error of the spanish regulator in the new Maritime Navigation Act, when repeating the provided posibility in the Spanish Civil Procedure Act, of a direct procedure of execution grounded on a extrajuditial enforcement such as the bill of lading. Finally, we would like to conclude the work studying the possible uses of Small Claim Procedure of the 812 article and followings of Spanish Civil Procedure Law, for the pur-pose of safeguarding credit, so as a short mention to other procedural figures expressly in-cluded in the Title IX of Maritime Navigation Law.
Aspectos procesales sobre Derecho Marítimo
Keywords: Derecho marítimo; Derecho procesal; Maritime law; Conocimiento de embarque; Bill of lading